Microsoft Office : gaining insight into the life of a college student. (A) - Sawhney, Mohanbir S. ([London] : SAGE, 2016)
Microsoft Office was facing an uphill task in engaging the undergraduate student community. Microsoft's past advertising efforts to reach this audience had proven lacklustre, while its key competitors were gradually entrenching themselves among this demographic. Microsoft's challenge was to determine the best tactics that could successfully connect with this audience. The case describes Microsoft's dilemma and briefly addresses what college students mostly care about: managing homework, creating great-looking schoolwork, preparing for the workplace and collaborating with friends and classmates.
Originally Published in: Sawhney, M., Ahluwalia, A., Gab, Y., Gardiner, K., Huang, A., Patel, A., & Goodman, P. (2012). Microsoft Office: Gaining Insight into the Life of a College Student (A). 5-111-011(A). Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 29, 2016).
Keywords: elektronické knihy; electronic books; Microsoft Corporation; Microsoft Office; Marketing research -- Case studies; Marketing -- Case studies